2018
DOI: 10.1088/1361-6455/aaa31c
|View full text |Cite
|
Sign up to set email alerts
|

Number-phase uncertainty and quantum dynamics of bosons and fermions interacting with a finite range and large scattering length in a double-well potential

Abstract: Abstract.In a previous paper [Das B et al. J. Phys. B: At. Mol. Opt. Phys 2013 46 035501], it was shown that the unitary quantum phase operators play a particularly important role in quantum dynamics of bosons and fermions in a one-dimensional double-well (DW) when the number of particles is small. In this paper, we define the standard quantum limit (SQL) for phase and number fluctuations, and describe two-mode squeezing for number and phase variables. The usual two-mode number squeezing parameter, also used t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Matter-wave phase operators were first introduced in 2013 [4]. It is shown that [4,5], for a low number of bosons or fermions, unitary nature of the phase-difference operators is important. For large number of photons or quanta, the non-unitary Carruthers-Nieto [13] phase-difference operators yield almost similar results as those due to Barnett-Pegg type unitary operator.…”
Section: Phase-operators: a Brief Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Matter-wave phase operators were first introduced in 2013 [4]. It is shown that [4,5], for a low number of bosons or fermions, unitary nature of the phase-difference operators is important. For large number of photons or quanta, the non-unitary Carruthers-Nieto [13] phase-difference operators yield almost similar results as those due to Barnett-Pegg type unitary operator.…”
Section: Phase-operators: a Brief Reviewmentioning
confidence: 99%
“…It is then necessary to formulate the quantum phase of matter-waves with a fixed number of particles. So, it is important to study quantum atom optics under the influence of unitary phase operators in matter-waves [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…lr corresponding to the cosine and sine, respectively, of the phase-difference between the left and right modes of the fermions (a ≡ F ) or bosons (a = B). These two operators do not commute with the population imbalance operator Ŵ = Nl − Nr where Nj = â † j âj for spinless bosons or Nj = σ=↑,↓ â † jσ âjσ for two-component fermions or bosons, leading to number-phase uncertainty relations [26]. It is theoretically shown that, these quantum phase operators are particularly important for matter-waves with low number of bosons or fermions, consistent with the similar result in case of photons as shown in [42].…”
Section: Entanglementmentioning
confidence: 99%
“…However, the properties of quantum entanglement and quantum fluctuations are found to be markedly different for a pair of spin-half fermions vis-a-vis a pair of spinless bosons. In terms of number and quantum phase variables, the number and phase squeezing properties are also different in two cases [26]. Quantum phase fluctuations are calculated using the recently introduced quantum mechanical phase operators for matter-waves [27].…”
Section: Introductionmentioning
confidence: 99%
“…Under tightbinding or two mode approximation, we describe in detail the effects of the range of interaction on the quantum dynamics and number-phase uncertainty in the strongly interacting or unitarity regime. We defined the standard quantum limit (SQL) for phase and number fluctuations and described two-mode squeezing for number and phase variables for this system [32].…”
Section: Introductionmentioning
confidence: 99%